Physical fitness profile of primary school learners in the Eastern Cape province of South Africa - Howard Gomwe; Lesego Phiri; Chioneso S. Marange (AOSIS, 2024)
Background: Low levels of physical activity in high- to low-income countries, including South Africa, pose a great risk of cardiovascular-related diseases. Aim: This study aimed to assess and compare the physical fitness profile among children. Setting: The study setting comprised rural and urban primary school learners in the Eastern Cape province, South Africa. Methods: A cross-sectional study was adopted utilising a randomly selected sample of boys and girls aged 9-14 years. Physical fitness measures were assessed using the Euro-fit test battery. Some parametric tests were used for mean comparisons of the various anthropometric measurements and physical fitness characteristics across demographics. Results: The sample consisted of 870 primary school learners. The average weight and height of the sample were 39.29 ± 10.34 kg and 144.06 ± 10.81 cm, respectively, with a mean body mass index (BMI) of 18.80 ± 4.11 kg/m2. The results showed that boys reported significantly high levels of physical fitness. Sit-ups (p ≤ 0.001) and VO2 max (p ≤ 0.001) significantly increase with age, while all the physical fitness measures were significantly higher among rural-based learners. Conclusion: Rural-based learners and boys generally had better physical fitness performance than their peers. The effect of gender and place of residence should be considered when designing physical fitness interventions. Contribution: This study adds to the existing body of knowledge about the effect of demographic factors on the physical fitness profile of children, where boys and rural-based learners are reported to be more physically fit than their counterparts.